ENTREPRENEURSHIP AND THE WELFARE OF FISHING COMMUNITIES: A CASE STUDY OF SAMBER VILLAGE, YENDIDORI DISTRICT, BIAK NUMFOR REGENCY - Loppies, Imelda Jaqualine; Syukur, Muh.; Firdaus W.Suhaeb (Gema Kampus IISIP YAPIS Biak, 2026)
This study examines the role of entrepreneurship in improving the welfare of fishing communities in Samber Village, Yendidori District, Biak Numfor Regency, Papua. Amid the vulnerabilities of capture fisheries and seasonal income fluctuations, local entrepreneurship has emerged as a strategic alternative for livelihood diversification. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that entrepreneurial activities—such as fish processing, small-scale trade, and community-based eco-tourism have contributed significantly to income enhancement, food security, and access to education. Moreover, entrepreneurship has fostered social empowerment, particularly among women and youth. However, challenges such as limited access to capital, low business literacy, and weak institutional support continue to constrain development. Despite these barriers, local actors demonstrate resilience through adaptive strategies based on social networks, traditional knowledge, and informal digital marketing. This study highlights the potential of community-based entrepreneurship to promote sustainable coastal development and recommends stronger support systems to scale its impact.